Efecto de dosis crecientes de npk en la acumulación de materia seca y algunas variables morfológicas en Ananas comosus (L.) Merr VARIEDAD ROJA TRUJILLANA. En un suelo ácido de Poroto, La Libertad. - Aguilar Castillo, Deyssi Sadith (2017)
From February 2014 to May 2016 it was evaluated at the National University of Trujillo, the effect of increasing doses of NPK in dry matter accumulation, some morphological variables and yield on Ananas comusus (L.) Merr. Var. Roja Trujillana in flower pot and field. In flower pot used a completely randomized design with 4 treatments (0-0-0; 200-60-400, 300-80-500 and 400-100-600 mg/kg suelo NPK) and 4 replications, the data subjected analysis of variance and for mean separation Tukey test was used at the 5%, each experimental unit consisted a flower pot with 5 kg of acid soil Poroto planted with fruit hijuelo base of 132 g. It was found that (i) 150 days after planting , low doses (200- 60-400) and medium (300- 80-500) form the upper NPK group in total dry matter accumulation, root dry matter , root fresh matter, total fresh matter, number and length of root, and (ii) high dose (400-100-600 mg /kg suelo) significantly reduces the total dry matter accumulation, root dry matter , root fresh matter, total fresh matter , the number and length root relative to low and medium doses under study. In field used a design randomized complete block with four treatments of increasing doses of NPK in kg ha-1 (150-100-200; 250-150-300; y 350-200-400) and a treatment with the farmer dose (250-100-250). It was found that the high dose of NPK dose exceeds the farmer used as a witness in yield (60.59 y 54.02 t.ha- 1), fruit weight at harvest (1.70kg.fruto-1 y 1.51 kg.fruto-1), and fruit weight after maturation process (1.67 y 1.48 kg.fruto-1) respectively, without being different from the medium and low doses.